Pengaruh Pembelajaran Kewirausahaan Terhadap Motivasi Berwirausaha - Prawiranegara, M R; Nuryanti, B. Lena; Mulyadi, Hari (Universitas Pendidikan Indonesia, 2018)
This study aims to (1) know the description of entrepreneurship learning, (2) find out the description of entrepreneurship motivation, (3) find out the effect of entrepreneurial learning on entrepreneurship motivation in class XI Bandung N 9 pastry majors in Bandung and (4) the relationship between entrepreneurial learning and motivation entrepreneurship for grade XI students majoring in SMK N 9 Bandung pastry. The object that becomes the unit of analysis in this study is the class XI students majoring in pastry at SMK N 9 Bandung .. The type of research used is descriptive, verification. The method used is explanatory survey with a sample technique that is a saturated sample technique with a sample of 100 respondents. The data analysis technique used is simple linear regression with SPSS 24.0 for Windows computer software tools. The findings in this study indicate that the picture of entrepreneurial learning in a good category, a picture of entrepreneurial motivation in a good category, motivation for entrepreneurship is positively influenced by entrepreneurial learning, and there is an active relationship or correlation between entrepreneurial learning and entrepreneurial motivation. Based on the results of this study it is recommended as a basis for conducting other studies regarding entrepreneurial learning and entrepreneurial motivation with different indicators and objects